Early endocytosis pathways in SSN-1 cells infected by dragon grouper nervous necrosis virus - Liu, Wangta; Hsu, Chi-Hsin; Hong, Yi-Ren; Wu, Shu-Chuan; Wang, Chun-Hsiung; Wu, Yi-Min; Chao, Chia-Ben; Lin, Chan-Shing (Journal of General Virology, 2005)
Many fish undergo betanodavirus infection. To study the infection process of dragon grouper nervous necrosis virus (DGNNV), native virus and virus-like particles (VLPs) were used to analyse the binding and internalization in SSN-1 cells. The binding of DGNNV and VLPs to SSN-1 cells was demonstrated using Western blotting and immunofluorescence microscopy. As estimated by indirect ELISA, the DGNNV particles bound SSN-1 cells in a dose-dependent manner up to 8×104 particles per cell. The binding of VLPs was sensitive to neuraminidase and tunicamycin, suggesting that cell-surface sialic acid is involved in binding. The penetration of DGNNV into cells, which was monitored by electron microscopy, appeared to occur mainly via the spherical pit and membrane ruffling pathways. Occasionally, a spherical pit was engulfed by membrane ruffling so as to form a large figure-of-eight-shaped vesicle with an open connection. Our observations suggest that DGNNV utilizes both micro- and macropinocytosis pathways to enter SSN-1 cells.